A study of subclinical hypothyroidism treated with alternate day fixed dose thyroxine therapy - Jhavar, Dharmendra; Naredi, Mohit (International Journal of Advances in Medicine, 2018)
Background: Subclinical hypothyroidism (SCH) is a biochemical diagnosis wherein free T4 is within normal range while serum TSH value >5mIU/L. We aimed to study effects of alternate day fixed dose thyroxine therapy on this subset of patients with a 3month follow up of various clinical and biochemical parameters. Methods: It was an interventional trial. Fifty consecutive consenting participants with SCH aged 18-45 years were started on alternate day 50µg thyroxine and were observed for 3 months for changes in body mass index, blood pressure, serum cholesterol, serum triglyceride, serum TSH, T3 and T4 levels. Results: Forty four out of fifty participants had initial TSH levels between 5-10 µU/mL and at the end of 3 months, 58% of these (n=29/44) shown improved thyroid profile as their TSH fell to the target 2-4 µU/mL. Seven participants’ (n=7,14%) turned into iatrogenic hyperthyroidism as their T3 and T4 levels rose above normal and TSH levels fell to below 1 µU/mL. Another 7 participants (n=7,14%) showed increased T3 and T4 levels (n=3, n=4 respectively) above normal range with TSH still within normal range. One patient (n=1,2%) had persistently raised TSH levels. Out of 6 participants (n=6,12%) who had initial TSH>10 µU/mL, 3 participants achieved normal TSH with alternate day therapy (n=3,6%) while 3 participants did not achieve euthyroid status (n=3,6%). Authors observed decrease in cholesterol levels (initial=183.18±52.96 mg/dL, final=170.04±42.13 mg/dL, p<0.05). It lead to reduction in weight (initial BMI=24.11±5.69, final=23.33±5.30, p<0.05). Conclusions: Authors found that treatment of SCH with alternative day thyroxine therapy is effective in normalizing TSH values. Its dose needs to be titrated according to TSH levels to avoid side effects. It decreased cost of therapy resulting in good compliance in noncompliant patients and reduced pill burden helped the patients in adhering to the therapy.